1987
DOI: 10.1002/etc.5620060708
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of selected bleached kraft mill effluent constituents on the sea urchin sperm cell

Abstract: The toxicities of chemicals found in bleached kraft pulp mill effluent were assessed using a sea urchin sperm toxicity test. Sperm of the purple sea urchin, Strongylocentrotus purpuratus, were preincubated with 12 individual compounds, including resin acids, unsaturated fatty acids, their chlorinated derivatives and chlorinated guaiacols. Sperm were then coincubated with eggs and inhibition of fertilization and the effects on sperm motility were assessed. Resin acids, which are highly toxic to juvenile salmoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…,scheri (Svenson et al, 1996). Unsaturated fatty acids were also major components of bleached kraft mill e%uent toxicity (Cherr et al, 1987;Crooks and Sikes, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…,scheri (Svenson et al, 1996). Unsaturated fatty acids were also major components of bleached kraft mill e%uent toxicity (Cherr et al, 1987;Crooks and Sikes, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Sperm was collected dry, directly from the surface of the sea urchins using a Pasteur pipette, and conserved in a small test tube at 4 • C. Indeed, as suggested by several authors, (D. Epel, personal communication; C. Falugi, personal communication; USEPA, 1995), the dry collection technique allows the sperm to be held longer without losing viability and decreases the sensitivity of a test because semen is more viable at the beginning of the exposure period (Anderson et al, 1990;Chapman, 1995;Cherr et al, 1987). In order to determine sperm concentration, 50 μl of semen were diluted and fixed in 9.95 ml fresh water and sperm count performed on a hemocytometer (Thoma chamber) under a microscope at 40×.…”
Section: Gametes Collection and Countsmentioning
confidence: 95%
“…Anderson (1983) previously demonstrated that copepods, which are an important part of the food web, are more sensitive to kraft mill effluent (LC50 = 12%) than juvenile salmonids (LC50 = 25%). The toxic effect of bleached kraft mill effluent constituents has also been demonstrated 214 using sea urchins (Cherr et al, 1987) and copepods (Renberg et al, 1980). Wu & Levings (1980) demonstrated that blue mussels and barnacles suffered reproductive impairment and slower growth rates when transplanted near the Port Mellon kraft mill outfall.…”
Section: Effects Of Effluent Toxicitymentioning
confidence: 98%